Struktur modal dan keberlangsungan lembaga keuangan mikro - Indayani Indayani; Imam Ghozali (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This study purpose to test the theory of capital structure (grants, equity, profits, savings, deposits, lingkage, subordinated loans and quasy capital) and its effect on sustainability in microfinance, particularly regulated institutions. The investigation involved a panel of 322 samples of conventional banks (BPR) throughout Indonesia for the period 2012-2014. The sampling method was based on proportional samples in the provinces/ districts. This research uses SEM analysis tool with WarpPLS to test hypothesis. Methods of data analysis were done by evaluating the measurement model and structural model. The results showed the equity, profit, savings and lingkage affected sustainability in microfinance. Meanwhile, grants, deposits, subordinated loans and quasy had no effect on the sustainability of microfinance. The implications of the policy show that savings and lingkage can be maintained and enhanced because they have an impact on improving the sustainability of the BPR. This research can be a reference for developing research related to the capital structure of microfinance in the future.